2023
DOI: 10.3390/biom13030488
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Physical Exercise Decreases Inflammation and Joint Damage in the Preclinical Phase of a Rheumatoid Arthritis Murine Model

Abstract: Lifestyle modifications in preclinical Rheumatoid Arthritis (RA) could delay the ongoing pathogenic immune processes and potentially prevent its onset. Physical exercise (PE) benefits RA patients; however, its impact in reducing the risk of developing RA has scarcely been studied. The objective was to describe the effects of low-intensity PE applied at the disease’s preclinical phase on the joints of DBA/1 mice with collagen-induced arthritis (CIA). Twelve mice with CIA were randomly distributed into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…One of the factors for the decrease in disease activity is presumed to be improvement in pain VAS. Although we could not evaluate levels of inflammatory cytokines, a study on mice with collagen-induced arthritis showed that low-intensity exercise decreased inflammatory cytokines such as tumor necrosis factor-α 25) . We believe that exercise therapy affects the improvement of conditions in RA.…”
Section: Discussionmentioning
confidence: 93%
“…One of the factors for the decrease in disease activity is presumed to be improvement in pain VAS. Although we could not evaluate levels of inflammatory cytokines, a study on mice with collagen-induced arthritis showed that low-intensity exercise decreased inflammatory cytokines such as tumor necrosis factor-α 25) . We believe that exercise therapy affects the improvement of conditions in RA.…”
Section: Discussionmentioning
confidence: 93%
“…Excessive mechanical stress on articular cartilage is a risk for osteoarthritis, whereas moderate mechanical stress is anabolic [24,25]. González-Chávez et al reported that low-intensity physical exercise decreases joint damage and the expression of RA-related genes and signaling pathways [26]. Shimomura et al reported that HIF-1α regulates aggrecan and ADAM-TS5 expression in response to mechanical stimulation under hypoxia and general mechanical stimulation in articular cartilage under hypoxia while controlling cartilage homeostasis [17].…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT pathway plays a crucial role in the inflammatory process of the synovium and bone destruction in RA 31 and is activated by upstream cytokines, such as IL-6 and IL-17, among others. 32 We evaluated pJAK-3 and pSTAT-3 protein expression by western blot from hind paw homogenates.…”
Section: Ola Diet Modulates Jak/stat Signaling Pathwaymentioning
confidence: 99%